“Evaluación del control interno en el departamento de créditos de la Cooperativa De Ahorro y Crédito Sumak Kawsay “del Cantón La Maná año 2019 - Palta Malagón, Andrea Carolina (2021)
The present research work with the theme "EVALUATION OF INTERNAL CONTROL IN THE CREDIT DEPARTMENT OF THE COOPERATIVE OF SAVINGS AND CREDIT SUMAK KAWSAY OF LA MANA CANTON YEAR 2019" aims to evaluate the internal control of the loan portfolio of the Cooperative of Savings and Credit Sumak Kawsay of the canton La Maná year 2019. It was to get appropriate work and objectives, can determine the risks or critical points that the cooperative contains at the same time. It is possible to solve problems of the entity concerning the delinquency in the credit accounts. In addition, the procedures evaluated and the critical areas identified to issue improvement proposals, according to the objectives that the cooperative must fulfill, thus preserving the resources against any loss due to mismanagement, errors, or irregularities. The methodology applied in this was descriptive research, it allowed to obtain specific information of the processes related to the policies in the credit area of the Cooperative to establish actions in front of the problematic found as well as methods and techniques such as Analytical Method and Deductive Method because specific conclusions formulated, for the construction of the exposed results. The internal control evaluation tool based on the COSO I model used for the application of the internal control questionnaire to gather information on the 5 components of the model, having as results a confidence level of the Internal Control System of 75.50%, while the Risk Level represents 22.50% considered as moderate Risk. The proposal proposes an internal control model as an alternative to establish the processes for delinquency control and portfolio recovery of the cooperative.